1955
DOI: 10.1002/cber.19550880714
|View full text |Cite
|
Sign up to set email alerts
|

Eine neue Methode zur Überführung von Mannich‐Basen in Aldehyde

Abstract: Nr. 7/1955] Thesing, M i i l l e r , Michel 1027 liert und das Destillat mit &,her extrahiert. Der &herriickstand wurde im Kugelrohr destilliert. Ausb. 250 mg Keton vom Sdp.,, 50° (Badtemperatur). Zur Reinigmg wurde an Aluminiumoxyd chromatographiert, die h k t i o n e n mit den reimten UV-Spektren wurden vereinigt und die Eindampfriicksthnde nochmala destilliert. hmar = 282.5 mp (E = 12800); IR-Spektrum (8. Abbild. 6). Dinitrophenylhydrazon: 50 mg Destillat wurden mit 200 mg Dinitrophenylhydmzin umgesetzt. Es… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

1955
1955
2012
2012

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(4 citation statements)
references
References 21 publications
0
4
0
Order By: Relevance
“…Under mild conditions and up to 2 molar excess, H 2 O 2 did not negatively impact the derivatization of reduced DMPO adducts nor did it suppress the detector response. Some reports have shown that acyclic HAs were oxidized by mildly acidic solutions of peroxides to the corresponding nitrones. On the other hand, in a biochemical system such as procarbazine/horseradish peroxidase (HRP) or MP-11, H 2 O 2 had a little effect on the final response. It is likely that these peroxidases caused a peroxide-catalyzed two-electron oxidation of the HAs.…”
Section: Resultsmentioning
confidence: 99%
“…Under mild conditions and up to 2 molar excess, H 2 O 2 did not negatively impact the derivatization of reduced DMPO adducts nor did it suppress the detector response. Some reports have shown that acyclic HAs were oxidized by mildly acidic solutions of peroxides to the corresponding nitrones. On the other hand, in a biochemical system such as procarbazine/horseradish peroxidase (HRP) or MP-11, H 2 O 2 had a little effect on the final response. It is likely that these peroxidases caused a peroxide-catalyzed two-electron oxidation of the HAs.…”
Section: Resultsmentioning
confidence: 99%
“…C6H6-N-CH2CHs -Ah c6h6-n=chch, + c6h5nhch2ch, + h2o I o Alkaline solutions of potassium ferricyanide were employed to prepare a-methyl-N-phenylnitrone (186,233) and other nitrones (97,221,223) from the corresponding hydroxylamines, often in high yields. 1-Hydroxypiperidine yielded upon treatment with potassium ferricyanide the trimer of 2,3,4,5-tetrahydropyridine N-oxide (223), while the same hydroxylamine upon cupric acetate catalyzed aerial oxidation yielded the dimer of 2,3,4,5-tetrahydropyridine Noxide (222).…”
Section: R-n-chr'r"mentioning
confidence: 99%
“…Quaternary Mannich bases when treated with an aromatic nitroso compound yielded nitrones. This reaction, although employed very seldom, was shown to be general (109, 177,221,226). Quinones yielded dinitrones upon treatment with nitrosobenzene (102), while various hydroxy lamine derivatives were found to disproportionate in carbon disulfide solution into nitrone and amine (186).…”
Section: F Miscellaneousmentioning
confidence: 99%
See 1 more Smart Citation